2018
DOI: 10.1371/journal.pone.0206705
|View full text |Cite
|
Sign up to set email alerts
|

The association of multiple anti-hypertensive medication classes with Alzheimer’s disease incidence across sex, race, and ethnicity

Abstract: BackgroundAntihypertensive treatments have been shown to reduce the risk of Alzheimer’s disease (AD). The renin-angiotensin system (RAS) has been implicated in AD, and thus RAS-acting AHTs (angiotensin converting enzyme inhibitors (ACEIs), and angiotensin-II receptor blockers (ARBs)) may offer differential and additional protective benefits against AD compared with other AHTs, in addition to hypertension management.MethodsIn a retrospective cohort design, we examined the medical and pharmacy claims of a 20% sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 55 publications
3
58
0
1
Order By: Relevance
“…Given the availability of potentially beneficial therapeutics and the lack of successful interventions for AD ( Edwards Iii et al, 2019 ), antihypertensive drugs have been explored as AD treatments. A retrospective cohort analysis of patients taking antihypertensive RAS-acting medicines, including angiotensin-converting enzyme inhibitors (ACEIs) and Ang II receptor blockers (ARBs), reported that AD incidence was lower in women (both Caucasian and African American) and Caucasian men taking ARBs compared with their counterparts not taking RAS-acting drugs ( Barthold et al, 2018 ). Furthermore, a meta-analysis found that controlling blood pressure with antihypertensive drugs in and of itself may have positive outcomes for cognitive function ( Ding et al, 2020 ).…”
Section: Vascular Contributors To Cognitive Impairment and Dementiamentioning
confidence: 99%
“…Given the availability of potentially beneficial therapeutics and the lack of successful interventions for AD ( Edwards Iii et al, 2019 ), antihypertensive drugs have been explored as AD treatments. A retrospective cohort analysis of patients taking antihypertensive RAS-acting medicines, including angiotensin-converting enzyme inhibitors (ACEIs) and Ang II receptor blockers (ARBs), reported that AD incidence was lower in women (both Caucasian and African American) and Caucasian men taking ARBs compared with their counterparts not taking RAS-acting drugs ( Barthold et al, 2018 ). Furthermore, a meta-analysis found that controlling blood pressure with antihypertensive drugs in and of itself may have positive outcomes for cognitive function ( Ding et al, 2020 ).…”
Section: Vascular Contributors To Cognitive Impairment and Dementiamentioning
confidence: 99%
“…Studies should include individuals with preclinical or early prodromal AD and plan a long follow-up period. As the association between antihypertensive drugs and AD may depend on sex, ethnicity and genetic background (APOE status), future therapeutic strategies will probably be personalized [148]. Recent evidence of the efficacy of polypills associating two antihypertensive drugs (diuretic and ACE inhibitor), statin, and aspirin came from a pragmatic trial in Iran, showing a reduction of the risk of major cardiovascular events.…”
Section: Expert Opinionmentioning
confidence: 99%
“…6 Subclasses most consistently associated with reduced dementia risk compared to other antihypertensives are angiotensin receptor blockers, certain calcium channel blockers, and diuretics. [6][7][8][9][10][11][12][13][14] The mechanisms underlying these differential effects are currently unclear. [6][7][8][9][10][11][12]15 They may be related to the renin-angiotensin system (RAS; Figure 1).…”
Section: Introductionmentioning
confidence: 99%